A5.12 Disappearance and Reappearance of IgG, IgA and IgM Autoantibody Isotypes and Immune Complexes in Rituximab-Treated SLE Patients. (25th February 2013) - Persson, Barbro; McAree, Fionnuala; Müller, Malin; Trollmo, Tina; Parodis, Ioannis; Jonsdottir, Thorunn; Malmström, Vivianne; Gunnarsson, Iva; Rönnelid, Johan
Abstract : Background and Objectives: We have earlier investigated the content of specific IgG autoantibodies in SLE immune complexes (IC; Åhlin et al, Lupus 2012; 21:586). For that purpose we have developed a line blot technique for the quantification also of non-classical (IgA and IgM) SLE autoantibody isotypes. In SLE patients, IgG autoantibody levels drop after institution of Rituximab therapy. The objective was to investigate parallel changes IgG, IgA and IgM autoantibody isotypes in parallel to IC levels. Materials and Methods: Nine SLE patients initially treated with two infusions of Rituximab were followed with repeated samplings at baseline and after 1, 3, 6 and 12 months. Thawed samples were investigated simultaneously concerning rheumatoid factor (RF) isotypes and C1q-binding IC with enzyme immunoassays. All samples from patients with ANA-associated autoantibodies (6/9) were investigated concerning IgG/A/M autoantibodies with line blot quantitated with densitometry and concerning IgG autoantibodies with ALBIA/Luminex technique. Significant changes were defined either as ≥33% drop or as ≥50% increase, compared to the lowest levels experienced during the follow-up period. Results: ALBIA measurements showed significant initial drop in anti-dsDNA in 4/6 patients but also significant drop in levels of anti-histone, anti-SSA/Ro60, anti-Sm and anti-Sm/RNP in individual patients. Late increases in IC and antibodies against dsDNA, SSA/Ro52, SSA/Ro60, SSB, Sm, Sm/RNP ribosomal P protein and histones were associated with clinical relapse. Late increase in IgA/IgM anti-DNA, anti-histones and anti-nucleosomes was also found in one patient with persistent kidney disease treated with mycophenolate mofetil at 10 months. Non-classical autoantibody isotypes showed late increases that often were not paralleled by the corresponding IgG autoantibodies. Two patients showed late increase in RF isotypes in parallel to clinical relapse. Different autoantibodies/isotypes showed different kinetics of appearance/disappearance. All ANA autoantibody positive patients initially had increased IC levels, which dropped significantly after therapy in 4/6 patients. The autoantibody negative patients never had increased IC levels and showed no significant changes in RF. Conclusions: Measurement of non-classical isotypes of RF and ANA-associated autoantibodies might yield clinically useful information when monitoring SLE patients treated with B cell depleting therapy.